Freedom of Religion in Jannah Al-Atfal (Heaven Of Children) The Works of Najib Mahfuz - Bermawy Munthe (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2014)
This study based on the theory of structuralism Robert Stanton, which focuses on the elements of theme in short story Jannah al -At fal (Children of Heaven) by Najib Mahfuz. The result of study was found that the etching of religious freedom to children as a religious education it’s aims to instill competency mastery of basic religious knowledge, attitude differences religious and religious tolerance, interfaith friendship, think and act freely, child relationship and God the Creator, child and the particulars of life and death as well as children and happenings in heaven and hell. This seventh aspect becomes interconnectivity and integrative unity to allow freedom of religion.